2014
DOI: 10.1002/cmr.a.21318
|View full text |Cite
|
Sign up to set email alerts
|

The bigger they are, the harder they fall: A topical review on sedimented solutes for solid‐state NMR

Abstract: Sample preparation for solid-state NMR of soluble proteins is all but a trivial accomplishment and often represents the factor that determines the success of the experiments, despite the dramatic methodological and technological improvements in the field of SSNMR. Several different sample preparation have been proposed and applied over the years, with varied results. Among those methods we have proposed the use of sedimentation for obtaining samples with high sensitivity and resolution. This review aims at cov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
6
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 132 publications
1
6
0
Order By: Relevance
“…Herein, it is shown that highly resolved ssNMR spectra can be obtained for PEGylated proteins in the pelleted state, a densely packed non‐crystalline state of a wet macromolecular sample, which can be obtained either by rehydration of freeze‐dried material, or by ultracentrifugation when allowed by the density and molecular mass of the molecule . Such high‐quality ssNMR spectra are suitable for extensive resonance assignment and even conventional full structure determination.…”
Section: Figurementioning
confidence: 99%
“…Herein, it is shown that highly resolved ssNMR spectra can be obtained for PEGylated proteins in the pelleted state, a densely packed non‐crystalline state of a wet macromolecular sample, which can be obtained either by rehydration of freeze‐dried material, or by ultracentrifugation when allowed by the density and molecular mass of the molecule . Such high‐quality ssNMR spectra are suitable for extensive resonance assignment and even conventional full structure determination.…”
Section: Figurementioning
confidence: 99%
“…Using solid-state Nuclear Magnetic Resonance (NMR), a wide variety of biological materials can be studied, such as micro-or nanocrystals, fibrillar aggregates, and proteins embedded in membranes. Sedimentation of dissolved proteins from the solution state directly into the magic-angle spinning (MAS) rotor has lately become the most important sample preparation approach for solid-state NMR (Bertini et al, 2011(Bertini et al, , 2012(Bertini et al, , 2013Gardiennet et al, 2012;Ravera, 2014;van der Wel, 2018;Lacabanne et al, 2019a). This can be achieved in an ultracentrifuge (Böckmann et al, 2009;Bertini et al, 2012;Gardiennet et al, 2012) using specially designed rotor-filling tools (Böckmann et al, 2009;Mandal et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Concentrations can be pushed even further by desalting proteins and using labile buffers, such as ammonium formate or ammonium acetate, which are also removed by vacuum during the lyophilization process. This preparatory technique has been used particularly heavily in solid-state NMR studies to investigate protein structure, sedimentation and solvation effects, and even metabolic pathways in whole cells [27][28][29][30].…”
Section: Introductionmentioning
confidence: 99%